Contribution of 2 D strain in the detection of subtle myocardial involvement in group A and B patients with chronic obstructive pulmonary disease - Kaddoussi, Rania; Chamtouri, Ikram; Dhouib, Wafa; Touil, Imen; Ben Abdallah, Saoussen; Daami, Monia; Elassoufi, Fatma Ezzahra; Jomaa, Walid; Rouetbi, Wissal; Turki, Ahmed; Ben Hamda, Khaldoun (Frontiers in Medicine, 2025)
BackgroundMyocardial involvement mediated by chronic obstructive pulmonary disease (COPD) is a common cause of morbidity and mortality. Conventional transthoracic echocardiography (TTE) parameters are poor in the detection of subclinical myocardial dysfunction.AimTo investigate the contribution of strain in the early detection of cardiac damage in clinically stable COPD patients.MethodsThis was a comparative study between COPD patients (classified A or B) with normal and reduced right ventricle (RV) strain. The COPD assessment test (e.g., CAT score), spirometry [e.g., forced expiratory volume in 1 s (FEV1, L)], 6 min walk test [e.g., 6 min walk distance (6MWD, m)], and both conventional TTE [i.e., left ventricular ejection fraction (LVEF), right atrium (RA), RV, left ventricle global longitudinal strain (LV GLS)], and strain (e.g., impaired RV strain is > −19), were performed.ResultsEighty COPD patients [mean ± standard deviation (SD): age = 66 ± 9 years, LVEF = 60.1 ± 5%, RA = 25 ± 7%, RV = −19.9 ± 3.7%, LV GLS v −21.1 ± 2, and 48% had impaired RV strain] were included. Compared to COPD patient with normal RV strain, those with reduced RV strain had (i) Lower 6MWD (310 ± 113 vs 470 ± 104 m; p = 0.001), (ii) Lower FEV1 (1.63 ± 0.73 vs 2.18 ± 0.41 L; p = 0.012), and (iii) Higher CAT score (21 ± 10 vs 13 ± 6; p = 0.012). An impaired RV strain was associated with a higher risk of hospitalizations for acute exacerbation in the post inclusion year, (respectively for 55% and 25%; p = 0.024). No death was recorded during the study period.ConclusionGroup A and B COPD patients having normal conventional TTE parameters, speckle tracking is a key parameter in the detection of subclinical myocardial dysfunction.